A Farmer Affordable Technique: Packaging with Nitrogen Gas (N2) Enhanced Shelf-Life of Fresh Oyster Mushroom (Pleurotus ostreatus) (Research in Agriculture Livestock and Fisheries, 2024)
The commercial viability of mushrooms in Bangladesh faces a challenge due to the mushrooms' short shelf life, arising from their high respiration rates, elevated moisture content, and the absence of a protective cuticular structure. To solve this problem, different ways of enhancing the packaging conditions have been explored. Our research focuses on the use of the inert gas, nitrogen, to extend the shelf life of Pleurotus ostreatus (oyster mushrooms). Nitrogen, being an inert gas, is assumed to ensure the preservation of the quality of fresh mushrooms. In our study, freshly harvested mushrooms were carefully packaged in polypropylene (PP) bags both with and without nitrogen gas. Which were then stored both at room temperature and in the refrigerator.  Throughout the storage period, the changes in seven quality parameters - total soluble sugar (TSS), browning index (BI), weight loss, pH, moisture content, odor, and texture were assessed at two-day intervals. The results revealed no significant changes in TSS or pH levels compared to the controls. Notably, mushrooms stored in PP bags having nitrogen and stored in the refrigerator exhibited improved quality over eight days, showing better results in BI, moisture content, and texture.Res. Agric. Livest. Fish. Vol. 11, No. 1, April 2024: 53-60